DEVELOPMENT MODEL OF DIGITAL-BASED DENTAL HEALTH RECORDING AND REPORTING SERVICE SYSTEM IN PUBLIC HEALT CENTER - Rizke Amalia Fauziah; Masrifan Djamil; Supriyana Supriyana (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
The Puskesmas Information Reporting System (SIP) has been in since 1981. In its implementation, SIP was still limited to data which was the result of interactions between the community and health facilities. Methods used Research and Development (RD). Collecting data by interview, observation, and documentation. The sample contained sample I amounted were 6 people, sample II were 25 people, and sample III were 16 people. Sampling technique with non probability sampling. Data analyswas used univariate and bivariate analyswas. Result that designed and built after being tested by experts, it was feasible to apply the Digital-Based Dental Health Recording and Reporting Service System Development Model. The Development Model of the Digital-Based Dental Health Recording and Reporting Service System after being tested has been proven to be relevant/suitable for use in the implementation of the digital-based dental health recording and reporting service system at the Puskesmas in Boyolali Regency. The Development Model of the Digital-Based Dental Health Recording and Reporting Service System has effective for the substance of the application system and improves the quality of the measurement before and after the development of a dental health recording and reporting service system based at the Puskesmas in Boyolali District with p value = 0.001. Conclusion that Development Model of the Digital-Based Dental Health Recording and Reporting Service System has effective for the substance of the application system and improves the quality dental health recording and reporting service system based at the Puskesmas.